Individual variation of the SARS‐CoV‐2 receptor ACE2 gene expression and regulation. Issue 7 (19th June 2020) - Chen, Jiawei; Jiang, Quanlong; Xia, Xian; Liu, Kangping; Yu, Zhengqing; Tao, Wanyu; Gong, Wenxuan; Han, Jing‐Dong J.
Abstract: The COVID‐19 coronavirus is now spreading worldwide. Its pathogen, SARS‐CoV‐2, has been shown to use angiotensin‐converting enzyme 2 (ACE2) as its host cell receptor, same as the severe acute respiratory syndrome coronavirus (SARS‐CoV) in 2003. Epidemiology studies found males although only slightly more likely to be infected than females account for the majority of the severely ill and fatality, which also bias for people older than 60 years or with metabolic and cardiovascular diseases. Here by analyzing GTEx and other public data in 30 tissues across thousands of individuals, we found a significantly higher level in Asian females, an age‐dependent decrease in all ethnic groups, and a highly significant decrease in type II diabetic patients of ACE2 expression. Consistently, the most significant expression quantitative loci (eQTLs) contributing to high ACE2 expression are close to 100% in East Asians, >30% higher than other ethnic groups. A shockingly common enrichment of viral infection pathways was found among ACE2 anti‐expressed genes, and multiple binding sites of virus infection related transcription factors and sex hormone receptors locate at ACE2 regulatory regions. Human and mice data analysis further revealed ACE2 expression is reduced in T2D patients and with inflammatory cytokine treatment and upregulated by estrogen and androgen (both decrease with age). Our findings revealed a negative correlation between ACE2 expression and COVID‐19 fatality at both population and molecular levels. These results will be instrumental when designing potential prevention and treatment strategies for ACE2 binding coronaviruses in general. Abstract : This study revealed the negative correlation of high basal ACE2 level with CoVID‐19 severity/fatality at the population level and its anticorrelation with virus infection pathway expression levels, upregulation by sex hormones and suppression by inflammatory cytokine at the molecular level.